GERAKAN PEDULI LINGKUNGAN DALAM PERSPEKTIF HUMAN SECURITY DAN KONSEPSI ISLAM DI KELURAHAN TIRTA SIAK KOTA PEKANBARU - Fatmawati Fatmawati; Rizal Effendi Putra; Rinah Rinah; Muhammad Irham (PT. Jurnal Center Indonesia Publisher, 2024)
One of the causes of environmental damage is the presence of piles of rubbish which can cause flooding and ultimately disrupt human survival. In Pekanbaru City, there are areas that have quite worrying waste problems, namely RT 03, RW 05, Tirta Siak Village, Payung Sekaki District, Pekanbaru City. Almost every day rubbish can be seen scattered in residential areas. This describes the lack of public awareness and concern regarding the importance of maintaining environmental cleanliness. The aim of this community service activity is firstly to provide knowledge of non-traditional threats, especially human security issue to residents of RT 03 RW 05, Tirta Siak Village, Payung Sekaki District, Pekanbaru City. Second, increase citizens' insight into Islamic conceptions of environmental cleanliness, and third, grow and increase citizens' awareness and concern in solving waste problems. Service activities start from the observation stage, carrying out counseling, recruiting volunteers, and monitoring. The result of this service activity is that residents' knowledge about the threat of environmental damage and good waste management techniques has increased. The increase in knowledge can be seen in the questionnaire results which reached 83%. Apart from that, residents' awareness and concern for environmental cleanliness is also starting to be seen from implementing the 4R concept in daily life and the formation of environmental care movement by carrying out routine mutual cooperation actions and monitoring the environment.